Compilation of seminar slides on pornography addiction module: a strategic and effective psychoeducational approach to optimise students’ mental & sexual health. - Uzir, Bisha Fathamah; Abdullah, Aszrin; Ahmad Basri, Nadzirah; Draman, Samsul (2022)
This compilation of seminar notes is a part of the intellectual property (IP) required to be produced under the allocation of KTP-RIGS21-057-0057 grant. The power point slides is prepared based on the needs and input required by the schools counselors all over Pahang. It is a compilation of 4 main topics delivered during the workshop conducted on 27th January 2022. This workshop is known as Program Pemindahan Ilmu (KTP), between Kulliyyah Farmasi IIUM and Jabatan Pendidikan Negeri (JPN) Pahang juga Majlis Guru-Guru Kaunseling Negeri Pahang (MGKK). The workshop was taken place through online medium , between 8.00am to 5.00pm and can the live record can be access via Kulliyyah of Pharmacy Facebook.